Boris: um broker para integração de serviços de saúde - Gondim, Bene Lemuel Dantas (Universidade Federal Rural do Semi-Árido, 2020)
Many hospitals, clinics and developers use web services applicable to health through websites, smartphone applications or through the use of cyber physical systems. Each of these services provides resources to the environment in which it operates. In this paper, a broker is proposed that allows interoperability among existing health systems, so that consumers can access resources independent of the representation and interface of a specific system. The broker allows the end user to access more resources within the same system, as well as simplifying the integration process among systems. The broker was developed based on an ontology, in which are described the applications that share their resources, and a web interface, through which consumers can look which resources are available and details about each one
Keywords: Saúde; Integração de sistemas; Broker; Ontologia; Health; Systems integration; Broker; Ontology; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO